Brexit, Englixit? Disintegration and How Taking Back Control Means Giving Up Control - O´Dubhghaill, Sean (2023)
This contribution seeks to explore what disintegration can mean for a language, with a focus on Brexit and the English language. Linguistic differences are often instrumentalized as drivers of disintegration. However, in the case of Brexit, disintegration will also affect the status of the English language. Due to the decision of the United Kingdom to leave the European Union, English will no longer be a first official language of any European member state; it is only the second official language in Ireland and Malta. This has important political and legal repercussions, that affect the future of the English language in the EU after Brexit. Based on desk research, we see two avenues for the future of the English language within the EU: it could be replaced by another major European language (German/ French), or could become a real European lingua franca. The latter option seems most reasonable as the English language has taken a firm foothold among young (and older) Europeans but entails that by taking back control of its decision-making processes by leaving the EU, the UK will lose the little control over the English language it currently still has. This tendency was already taking place both internationally as within the EU but will greatly accelerate after Brexit.